Research and application of 5G cloud-network-edge-end integrated in-depth security protection system - Guoxin ZHANG (Dianxin kexue)
A 5G cloud-network-edge-end integrated in-depth security protection implementation scheme was innovatively proposed, the network security protection system of 5G customized network was explored, and the basic architecture, characteristics, implementation scheme and application effect of the system were introduced.In the implementation plan, two key points were emphasized.Firstly, by deploying the security system of the four aspects of the 5G cloud network, the edge and the end, the multi-level and multi-dimensional security protection capability was formed.Secondly, the operation process of the adaptation system, including one-key reinforcement, security defense, situational awareness and one-key emergency response was established.Finally, the practical application effect of the 5G cloud-network-edge-end integrated in-depth security protection system was given.